Determinants of life insurance demand: an empirical investigation in the Malaysian market - Zatul Karamah Ahmad Baharul-Ulum; Lim, Thien Sang; Amer Azlan Abdul Jamal (Society for Business and Social Sciences, 2012)
The objectives of this article are to examine the determinants and relationship of economic variables towards the demand of life insurance policy in Malaysia. Based on the data sample from 1991 to the recently 2010, the empirical analysis proved that the three main factors which have influenced the life insurance demand are associated firstly with the roles played by the individual’s available expenses, secondly the short-term interest rates and finally the growth of an economy. The findings also highlights that consistent with previous research findings, the demand increases with individual’s available expenses and economic growth, and decreases with the condition of short-term interest rates in the market.